Supply chain cost management : the AIM & DRIVE process for achieving extraordinary results - Anklesaria, Jimmy (AMACOM, American Management Association, 2008)
"Supply Chain Cost Management will give you the tools you need to take the exorbitant costs from your supply chain, while improving your customer relationships and sharpening your competitive edge. Filled with examples of companies that have made this process work, this book outlines some of the problems with cost management today and lays out a checklist for successfully implementing the process. With a straightforward, easy-to-understand approach, author Jimmy Anklesaria walks you through the eight-step AIM & DRIVE process, and shows you how to select the right team to develop strategies and set goals, identify critical costs, and develop and define a comprehensive list of cost-drivers. Following the concepts of cost management, he shows how any company can gain the kind of efficiency and cost-advantage that Toyota, Honda, and John Deere have enjoyed for years."--Jacket